2005
DOI: 10.1016/j.procbio.2004.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Fate of phthalic acid esters during composting of both lagooning and activated sludges

Abstract: Among the phthalic acid esters (PAEs) targeted by the United States Environmental Protection Agency (USEPA) as priority pollutants, diethyl-hexyl phthalate (DEHP) is the major pollutant identified at high concentration level in lagooning sludge (LS), at about 28.67 mg/kg, and in activated sludge (AS), at about 6.26 mg/kg. Other phthalic acid esters, such as di-butyl phthalate (DBP) and di-methyl phthalate (DMP) show very low concentrations. During sludge composting, after the stabilization phase, the subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(76 citation statements)
references
References 37 publications
4
70
2
Order By: Relevance
“…Many clear-zone-forming cells were observed from bacteria isolated from both the fi rst and fourth activated sludge tanks, but no more than 10 cells/ml were observed in the infl ux water and the sludge drainage water. These results indicate that there were many DBP-degrading cells in the activated sludge, which confi rms previous studies about biodegradation of DBP using activated sludge (Amir et al, 2005;Roslev et al, 2007;Wang, 2004). Therefore, we suspect that samples of activated sludge from other locations also would likely contain Dibutyl phthalate-degrading bacteria from hydrospheres DBP-degrading bacteria.…”
Section: The Number Of Clear-zone-forming Cells In Activated Sludgesupporting
confidence: 90%
“…Many clear-zone-forming cells were observed from bacteria isolated from both the fi rst and fourth activated sludge tanks, but no more than 10 cells/ml were observed in the infl ux water and the sludge drainage water. These results indicate that there were many DBP-degrading cells in the activated sludge, which confi rms previous studies about biodegradation of DBP using activated sludge (Amir et al, 2005;Roslev et al, 2007;Wang, 2004). Therefore, we suspect that samples of activated sludge from other locations also would likely contain Dibutyl phthalate-degrading bacteria from hydrospheres DBP-degrading bacteria.…”
Section: The Number Of Clear-zone-forming Cells In Activated Sludgesupporting
confidence: 90%
“…Another known example is the composting of both lagooning and activated sludges, which is a method often used to treat pollutants. Such a process is always done at relatively high temperatures to keep the reaction effective (18). Therefore, it is valuable to study the enzymes that are active and stable under such high-temperature circumstances.…”
mentioning
confidence: 99%
“…Low pH during composting in R3 could be possibly explained by the acidic nature and high buffering capacity of corncob, which may have prevented increase of pH. In a study conducted by Amir et al (2005), similar values were observed for the final compost in composting studies that used wastewater treatment sludge. The EC can be used as an indirect method to evaluate the degree of salinity in the composting mixture, which indicates its possible phytotoxic/phytoinhibitory effects on plant growth after application to the soil (Lin, 2008).…”
Section: Temperaturementioning
confidence: 59%